Capacity sharing on the sustainability of vegetable farms in Benin - Fassinou Hotegni, V. Nicodeme (CGIAR, 2024)
A workshop was held on 12 and 13 September to share the findings of the study “Assessing sustainability in smallholder vegetable farms in Benin Republic: A matrix approach” with extension agents and provide them with better information and skills on approaches to measuring farm sustainability. The workshop, which was attended by 16 agents from Development Poles 1 and 7 (major vegetable production regions in the country), was held on the GBioS premises at the University of Abomey-Calavi. After exploring the theoretical aspects of the IDEA (Indicateurs de Durabilité des Exploitations Agricoles) approach, and the results of its application to vegetable production systems in Benin, participants were given the opportunity to apply the IDEA approach to a real life-setting (GBioS demonstration site). This was an opportunity for the participants to gain a practical understanding of how to collect, analyze and interpret data in order to better support farmers in improving their farming practice. A guided tour of the various technical platforms of GBioS and the World Vegetable Center research station, led by Dr Mathieu Ayenan, gave participants a close-up view of research on vegetable variety development and good agronomic practices. The workshop covered various aspects of the sustainability of production systems, including ecological sustainability, social sustainability and economic sustainability. The participants confirmed that the results of the study reflected the reality on the ground and understood that sustainability takes into account three dimensions: environmental, social and economic. For the participants, this workshop provides the tools to understand and apply the various practices in the field so as to better support producers in the transition to more environmentally-friendly practices while guaranteeing their economic and social viability. The current document stands for the technical report of this capacity-sharing workshop.